Sentiment Analysis of Sharia Banking in Indonesia - Windiantoro, Windiantoro; Bintoro, Bambang Purwoko Kusumo (The Indonesian Journal of Business Administration, 2015)
Abstract.Sharia banking in Indonesia is currently under growing phase. In year 2008-2012, the growth of assets, financings, and deposits increased more than 30 pecent. With its 200 million people, Indonesia is one of the countries with the biggest muslim population in the world. This shows that sharia banking industry in Indonesia has a great potential to grow even more. On the other hand, banking penetration level and sharia banking market share of Indonesia ranked last among countries with major muslim population. Based on statistics issued by OJK, sharia banking in Indonesia spent around 392 billion rupiahs annualy for promotion. This should contribute positive effect toward awareness and perception of people in sharia banking. One way to monitor promotion’s performance is by extracting and analyzing opinion and sentiment of people in the form of social media.The methodology used in this final project is divided into three parts: survey, crawling to social media, and sentiment analysis. Survey is performed to gain the insight of public opinion regarding concepts or terminologies related to sharia bank. This insight will become the input for crawling activity to social media.The result of activity in mentions from social media will then be processed using sentiment analysis to observe public’s sentiment of sharia bank. This research shows the facts that awareness level of public in sharia bank is still low, and people mostly relate sharia bank with Islam and its law. Sentiment analysis showed that people has positive sentiment tendency for sharia bank, but the low number of mentions gained made it difficult to gain more insight.Based on the result of this research, it is recommended for sharia banking industry to focus in raising awareness level of public to sharia bank. Hopefully, the insight gained from this project can be used as an input for designing marketing strategy for sharia banking industry in Indonesia. Keywords: Sharia banking, sentiment analysis, marketing